Increments in cytokines and matrix metalloproteinases in skeletal muscle after injection of tissue-damaging toxins from the venom of the snake Bothrops asper - Alexandra Rucavado; Teresa Escalante; Catarina F. P. Teixeira; Cristina María Fernándes; Cecilia Díaz; José María Gutiérrez (Mediators of Inflammation)
Envenomations by the snake Bothrops asper are characterized by prominent local tissue damage (i.e. myonecrosis), blistering, hemorrhage and edema. Various phospholipases A2 and metalloproteinases that induce local pathological alterations have been purified from this venom. Since these toxins induce a conspicuous inflammatory response, it has been hypothesized that inflammatory mediators may contribute to the local pathological alterations described. This study evaluated the local production of cytokines and matrix metalloproteinases (MMPs) as a consequence of intramuscular injections of an Asp-49 myotoxic phospholipase A2 (myotoxin III (MT-III)) and a P-I type hemorrhagic metalloproteinase (BaP1) isolated from B. asper venom. Both enzymes induced prominent tissue alterations and conspicuous increments in interleukin (IL)-1β, IL-6 and a number of MMPs, especially gelatinase MMP-9, rapidly after injection. In contrast, no increments in tumor necrosis factor-α (TNF-α) and interferon-γ were detected. In agreement, MT-III and BaP1 did not induce the synthesis of TNF-α by resident peritoneal macrophages in vitro. Despite the conspicuous expression of latent forms of MMPs in muscle, evidenced by zymography, there were no increments in activated MMP-2 and only a small increase in activated MMP-9, as detected by a functional enzymatic assay. This suggests that MMP activity was regulated by a highly controlled activation of latent forms and, probably, by a concomitant synthesis of MMP inhibitors. Since no hemorrhage nor dermonecrosis were observed after injection of MT-III, despite a prominent increase in MMP expression, and since inflammatory exudate did not enhance hemorrhage induced by BaP1, it is suggested that endogenous MMPs released in the tissue are not responsible for the dermonecrosis and hemorrhage characteristic of B. asper envenomation. Moreover, pretreatment of mice with the peptidomimetic MMP inhibitor batimastat did not reduce myotoxic nor edema-forming activities of MT-III, suggesting that MMPs do not play a prominent role in the pathogenesis of these effects in this experimental model. It is concluded that MT-III and BaP1 induce a local inflammatory response associated with the synthesis of IL-1β, IL-6 and MMPs. MMPs do not seem to play a prominent role in the acute local pathological alterations induced by these toxins in this experimental model.